Changes in Physicochemical Properties of Rice During Storage - Villareal, R.M.; Resurreccion, A.P.; Suzuki, L.B.; Juliano, Bienvenido O. (Wiley, 1976)
The changes in the physicochemical properties of rices which had different amylose contents were studied when the rice was stored at 2°C and 29°C as rough rice, milled rice, defatted milled rice, and as starch. Changes in hardness index, water absorption, stickiness, viscosity, salt‐soluble protein, free fatty acids, and carbonyl compounds during storage are discussed.